Analysis Sentiment of Nestle Bear Brand during the Covid-19 Pandemic on Social Media Twitter - Fauzan Kamil; Arga Hananto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Position and brand image are important and crucial in marketing strategy. Brand position and image form strong associations with targeted consumers used to differentiate a brand from its competitors. Companies must understand good marketing strategies to improve their brand position in society based on consumer perspective. During the Covid-19 pandemic, especially in 2021, there was a unique phenomenon, whereby the demand for Bear Brand Milk was greater than the market leader, namely Ultra milk, while Ultra milk was even cheaper than the Bear Brand milk. This phenomenon is discussed on social media, especially Twitter regarding opinions from consumers in purchasing the products. This study aims to determine whether online text reviews can provide an overview of the position and brand image of Bear Brand Milk using LIWC (Linguistic Inquiry and Word Count) sentiment analysis and PCA (Principal Component Analysis). Based on our analysis, we can conclude that LIWC can provide an overview regarding the brand image and brand positioning of Bear Brand milk and Ultra milk. Brand image is obtained from variables that describe psychological variables when using or imagining the brands. Brand Position through PCA analysis describes the difference in gain between the dominant variables in the two brands.